THE REPRESENTATION OF GENDER IN DISNEY’S SNOW WHITE AND THE SEVEN DWARFS AND MIRROR MIRROR MOVIE - R. Dinda S Nurfadilla S; Jauhar Helmie (Universitas Muhammadiyah Semarang, 2018)
The present study entitled The Representation of Gender in Disney’s Snow White and the Seven Dwarfs and Mirror Mirror Movie aims at investigating the gender stereotypes representation in both of the movies using the chosen theory of gender stereotypes aspects by Golombok and Fivush (1994), also analyzing the gender development traits ascribed to character of Snow White in the movies. This study uses descriptive qualitative approach in relation to investigate and analyze the object material which are Snow White and the Seven Dwarfs (1937) and Mirror Mirror (2012) movies. The data were gained by doing observation. And to figure out the research question, the writer uses content analysis and employs the theory of gender stereotypes aspects (Golombok and Fivush, 1994) which are physical appearance, personality traits, attitudes and interest, social relations and occupation. This study uncovers the gender representation ascribed to Snow White in two version of the movies. The result shows that, in the first version, Snow White and the Seven Dwarfs (1937) is still presented gender stereotypes by ascribing femininity to Snow White, the character imaged as domestic, dependent and weak character. And Snow White experienced the gender development representation and the changing image of woman in Mirror Mirror (2012), on the movie Snow White is no longer images as before,dependent and weak but more likely to have a strong and brave character. Keywords: gender representation, woman image, Snow White, content analysis